Peningkatan Motivasi dan Hasil Belajar Siswa pada Materi Akhlak Terpuji "Jujur dan Amanah" melalui Model Problem Based Learning di Kelas VII MTs Negeri 2 Pasaman - Susanti, Naimah (Journal of Development Education and Learning (JODEL), 2025)
This classroom action research addresses the low motivation and learning outcomes in Aqidah Akhlak among seventh-grade students at MTsN 2 Pasaman, focusing on the moral values of honesty and trustworthiness. The study aims to enhance student motivation and cognitive mastery by implementing Problem-Based Learning (PBL). The research employed a two-cycle PTK (Kemmis & McTaggart): planning, action, observation, and reflection. The sample consisted of 25 students. Data were collected via tests, motivation questionnaires, observation sheets, and documentation. After Cycle I (honesty) and Cycle II (trustworthiness), student motivation increased from 72% to 92% and learning completeness from 60% to 96%. Conclusions: PBL effectively enhances both the motivation and learning outcomes for Aqidah Akhlak by engaging students in contextual problem solving.